HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN PERKEMBANGAN MOTORIK PADA BAYI - Nurlaila, N; Riyatun, Kholifah; Iswati, Ning (Jurnal Ilmiah Kesehatan Keperawatan, 2017)
Motoric development is the beginning of intelligence and social emotion on the baby. Environment factors hold the main role of growth and development on baby, one of them are nutritional aspects. Administration of adequate nutrition would influence growth and development on baby optimally. This purpose of research to know the relationship between exclusive breastfeeding with motoric development in the baby. This study used the correlative description with the cross-sectional approach. As much 35 respondents joined with the criteria inclusion age baby at 6-18 months. Purposive sampling technique applied in this study. Collecting data used questionnaire named Denver II.Â  Data analysis using Chi- Square correlation test. The result based on Chi-Square correlation test, showed significance p = 0.000. It means that there was the relationship between exclusive breastfeeding with motoric development in the baby. The conclusion, there was the relationship between exclusive breastfeeding with motoric development in the baby. The nurse should conduct health promotion about the enhancement of exclusive breastfeeding and mother attitude into the baby development